INFLUENCE OF ADVERTISEMENT AMONG YOUNGSTERS IN USING COSMETIC CARE PRODUCTS- A STUDY WITH SPECIAL REFERENCE TO CHENNAI CITY - Rajya Lakshmi. K, Dr. R. Lakshmi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The goal of the paper is to analyse the influence of advertisement on top of retail performance of college students Methodology: Study will be taken in Chennai city. Sample size 200. Research technique: The study was based on Quantitative technique Tools Used: Percentage analysis, Descriptive Statistics, ANOVA, Regression were used Conclusion: The existing users of the products and services be contented with their manufactured goods and provision, and followed by convenient are the probability of reference to the recent ones. Business organization is to understand the desires and anxiety of the consumers in addition to how to put on fidelity for the successful business. Every satisfied consumer is the resources and making the possibility of the new consumer